Examination of university students' partner selection priorities - Kabaklı Çimen, Latife; Çimen, Latife Kabaklı (Kadir Ulusoy, 2018)
This research is a descriptive study in which the spouse selection priorities of university students are examined in the context of specific data. The study group of the research consists of 384 participants studying at various departments of a foundation university in Istanbul of the 2016- 2017 academic year. The data were obtained using the assessment tool for Priorities in Spouse Selection and the Personal Information Form. According to the results of the study, the spouse selection priorities of the students that participated in the study are listed as being tolerant/sensitive/sympathetic, being of the same religion/sect, and not having been married before. While males paid more attention to being tolerant/sensitive/sympathetic among the characteristics of a prospective spouse than females, females paid more attention to the quality of being of the same religion/sect than males. It was determined that single students preferred that a prospective spouse was tolerant/sensitive/sympathetic, married students preferred that a prospective spouse was of the same religion/sect. Both third-grade and fourth-grade students preferred that a prospective spouse was tolerant/sensitive/sympathetic in the first place. Students in the age group of 18-25 years and at the age of 26 and above preferred that a prospective spouse was tolerant/sensitive/sympathetic. While students with high-income level preferred that a prospective spouse had not been married before, students with middle-income level preferred that a prospective spouse was tolerant/sensitive/sympathetic. While those with a monthly expense of 1000 TL and below, and between 1001 and 2000 TL preferred that a prospective spouse was tolerant/sensitive/sympathetic, those with a monthly expense of 2001 TL and above preferred the quality of being skilful/talented/hard-working. While those who planned to get married by experiencing a romantic relationship/flirting or dating preferred that a prospective spouse was tolerant/sensitive/sympathetic, those who planned to marry through an arranged marriage preferred that a person whom they would marry was religious

Bu araştırma, üniversite öğrencilerinin eş seçme önceliklerinin incelendiği betimsel bir çalışmadır. Araştırmanın çalışma grubunu, 2016-2017 Eğitim-Öğretim Yılında İstanbul’da bir vakıf üniversitesinin 384 öğrencisi oluşturmaktadır. Veriler, Kişisel Bilgi Formu ve Eş Seçme Öncelikleri ölçme aracı ile elde edilmiştir. Araştırma sonuçlarına göre; öğrencilerin eş seçimi öncelikleri; hoşgörülü/duyarlı/cana yakın olmak, aynı dinden/mezhepten olmak ve daha önce evlenmemiş olmak şekilde sıralanmaktadır. Erkekler eş adayının hoşgörülü/duyarlı/cana yakın olmasını kadınlardan daha fazla önemserken, kadınlar aynı dinden/mezhepten olma özelliğini erkeklerden daha fazla önemsemiştir. Bekarların eş adayının; hoşgörülü/duyarlı/cana yakın olmasını, evlilerin ise aynı dinden/mezhepten olmasını tercih ettikleri belirlenmiştir. Hem üçüncü sınıf hem de dördüncü sınıf öğrencileri eş adayının hoşgörülü/duyarlı/cana yakın olmasını ilk sırada tercih etmiştir. 18-25 yaş grubu ve 26 yaş ve üstü öğrencileri eş adayının; hoşgörülü/duyarlı/cana yakın olmasını tercih etmişlerdir. Maddi gelir seviyesi yüksek olan öğrenciler eş adayının daha önce evlenmemiş olmasını, maddi gelir seviyesi orta düzeyde olan öğrenciler eş adayının hoşgörülü/duyarlı/cana yakın olması özelliğini tercih ettikleri görülmüştür. Aylık harcaması 1000 TL ve altı ile 1001-2000 TL arası olanlar eş adayının hoşgörülü/duyarlı/cana yakın olmasını tercih ederken, aylık harcaması 2001 TL ve üstü olanların becerikli/yetenekli/ hamarat olma özelliğini tercih ettikleri görülmektedir. Aşk ilişkisi/flört ederek veya tanışarak evlenmeyi planlayanlar eş adayının hoşgörülü/duyarlı/cana yakın olması tercih ederken; görücü usulü ile evlenmeyi planlayanlar eş adaylarının dindar olmasını tercih ettikleri belirlenmiştir.
Üniversite öğrencilerinin eş seçme önceliklerinin incelenmesi
Keywords: Marriage; Family; University student; Spouse selection; Culture; Evlilik; Aile; Üniversite öğrencisi; Eş seçme; Kültür